Interpreting the Erotic as An Agency: A Study of Haruki Murakami’s Norwegian Wood - Smaranika Chakraborty; Himangshu Sarma (IAFOR Journal of Arts & Humanities)
The primary aim of our study is to challenge the traditional phallocentric conception of the erotic that casts women as passive objects, whose sexuality is defined solely in relation to the phallus. Drawing on the feminist critique of Audre Lorde, who contends that the power of the erotic is an empowering force that is latent in women, we argue that when women take agency over their body and reclaim their sexuality, they emerge as empowered beings in all aspects of their lives. The erotic, thus, turns into a life force or a creative agency to address the multifariousness of sexuality. This paper seeks to establish the trope of erotic as a constructive force and further aims to explicate how women wield sexuality to subvert gendered power dynamics and counter the historical use of sexuality as a tool for female subjugation. By integrating Lorde’s idea of the erotic as an agency along with the theories of sexuality propounded by Herbert Marcuse, Luce Irigaray, and Georges Bataille, we attempt to arrive at an alternative conceptualization of the erotic through a feminist reading of Haruki Murakami’s Norwegian Wood (2003) and perceive the sexual encounters in question, as an empowering and reconciling force for both the sexes, rather than perpetuating power dynamics.